The Role of GitLab Runners in CI/CD Pipelines: Configuring EC2, Docker, and Kubernetes Build Environments - Koneru, Naga Murali Krishna (The Eastasouth Journal of Information System and Computer Science, 2025)
This research studies GitLab Runners optimization in CI/CD pipelines across the EC2, Docker, and Kubernetes environment configurations. It shows that such key strategies for enhancing build performance and resource utilization would reduce build time by 65 percent and resource costs by 40 percent. Practical recommendations for configuring runners to achieve optimal efficiency are presented in the context of analyzing 200 enterprise pipelines. The key optimization techniques are autoscaling based on real-time metrics, advanced caching to minimize the rebuilds, and tuning the resource allocation to avoid over-provision. The study further looks into the capability of machine learning models to optimize the number of runners dynamically, predict the hit or not on the cache, and automatically pick up the execution environment. When these innovations are applied, CI / CD pipeline performance will improve by reducing idle resources, building time, and optimizing resource utilization. The paper shows that experts can achieve very good availability and cost efficiency by adapting the configuration of GitLab Runners. The research also discusses the evolution of automated environment selection and machine learning-based performance tuning. This framework serves as the base for organizations to increase their CI/CD pipeline development rate and facilitates a faster, more reliable, and cheaper software delivery.